Continuous, Ultra-high Resolution WAIS-Divide Ice Core Methane Record 9.8-67.2 ka BP - Mcconnell, Joseph; Brook, Edward J; Rhodes, Rachel (IEDA: US Antarctic Program Data Center, 2015)
Abstract: This data set contains methane concentrations from a West Antarctic Ice Sheet (WAIS) Divide ice core obtained by an online, continuous technique (Stowasser, et al. 2012). IMPORTANT NOTE: The experiment-time-integrated data are made available as a comprehensive archive of WAIS-Divide methane measurements. In the vast majority of cases the 2-yearly spline fit will be the most suitable for your application (Rhodes_Science_2015_WD_CH4_noaa-wdc-paleo (8).xlsx or Rhodes_Science_2015_WD_CH4_noaa-wdc-paleo.txt). For more detailed information on the 2 yearly cubic smoothing spline please refer to references listed, in particular, the Supplementary Material of Rhodes et al. (2015).